Association of microbial translocation biomarkers with clinical outcome in controllers HIV-infected patients. (27th March 2015) - León, Agathe; Leal, Lorna; Torres, Berta; Lucero, Constanza; Inciarte, Alexy; Arnedo, Mireia; Plana, Montserrat; Vila, Jordi; Gatell, Josep M.; García, Felipe
<x xml:space="preserve">Abstract</x> Background: A proportion of patients who spontaneously control viral load (controllers) experienced clinical progression. We hypothesized that microbial translocation would independently determine the rate of disease progression in controllers. Methods: sCD14, lipopolysaccharide-binding protein (LBP) and EndoCab levels were assessed in 114 antiretroviral-naive patients with CD4+ T cells above 500 cells/μl (including 63 controllers and 51 noncontrollers). The independent predictive value of these markers on time to progression to the combined endpoint of AIDS, non-AIDS event, initiation of combination antiretroviral therapy (cART) or CD4+ cell count less than 500 cells/μl was assessed using a Cox regression model. Results: Most of the patients progressed to a combined endpoint (60%). Clinical progression in controllers was significantly lower than in noncontrollers (P = 0.02). Controllers with lower than the median baseline CD4+ T-cell count and higher than the median baseline viral load, sCD14 and EndoCab levels had a worse prognosis (P < 0.0001, P = 0.007, P = 0.05 and P = 0.012), while noncontrollers with higher than the median baseline LBP level also had a worse prognosis (P = 0.019). sCD14 and LBP increased and EndoCab decreased over time [from baseline (median values: 1486, 17604 ng/ml and 68 MMU/ml, respectively, to the date of event or the last determination (median values: 1663, 20230 ng/ml and 49 MMU/ml), respectively] in controllers (P = 0.04, 0.08 and 0.0006, respectively). Conclusion: Microbial translocation seems to be an important determinant of clinical progression in HIV-infected controllers independently of viremia. Measures to improve the intestinal mucosa damage or decrease translocation could influence the outcome in these patients.